TELAAH KRITIS METODOLOGI ISTINBATH MUI (STUDI KASUS FATWA TENTANG GOLPUT) - Iffatul Umniati Ismail (Sharia and Law Faculty, 2017)
This essays is dealing with manhaj istinbat al-ahkÄm, or Methodology of Islamic Legal Fatwa inferences, that has been implemented by Indonesian Islamic Jurist Council (Majelis Ulama Indonesia, and then would be calledâ€the MUIâ€™s Methodologyâ€), with particular reference to its fatwa on prohibition of Absentia Voters in the election as the specific object of this study. This study has found the MUIâ€™s Methodology could be categorized â€“ as being known in Islamic Legal system â€“ as â€œthe Collective Ijtihadâ€ with a narrow participation of Indonesian Ulamas only, and none of International Ulama was officially involved. This study has made efforts to explore the ways MUIâ€™s Methodology has been implemented, and then to reconstruct some ideal parameters of the Islamic Legal Fatwa Inferences Concept according to the basics of Islamic Jurisprudential system. As the study examines too the MUIâ€™s Methodology as implemented on the specific object of this study. The fatwa was decided by All-Indonesia Legislation Forum of The Committees of Fatwa that being held in Padang, January 26, 2009.